An Interactive Curriculum Increases Confidence in Identification and Management of Gynecologic Office Emergencies [A55]. (May 2022) - Maciejko, Laura; Cope, Adela; Bell, Shannon L.; Scheib, Stacey A.; Galhotra, Sheena; Green, Isabel
Abstract : INTRODUCTION: Emergencies during gynecologic office procedures are uncommon. However, knowledge in management of these complications is essential as more gynecologic procedures move from the operating room to the office. Our goal was to develop an interactive curriculum to address a gap in residency training in the management of office-based procedural emergencies. METHODS: A curriculum including management of unanticipated bleeding, anaphylaxis, vasovagal response, and local anesthetic systemic toxicity (LAST) was developed and implemented using a combination of simulated patient sessions, a "choose-your-own-adventure" PowerPoint, and a mock oral board session. Pre and post intervention surveys queried participants' confidence in recognition and management. The curriculum was delivered as in-person simulation sessions or virtual sessions due to COVID restrictions. Institutional review board (IRB) approval was obtained. Mean pre and post intervention scores were compared using paired t-test. RESULTS: Four accredited obstetrics and gynecology residency programs participated. Twenty-nine trainees completed the curriculum, and 24 submitted pre and post surveys (82.8% response rate). There was significant improvement in confidence scores for management of unanticipated bleeding (mean difference 0.96, P <.001), anaphylaxis (mean difference 1.7, P <.001), vasovagal response (mean difference 1.0, P <.001), and LAST (mean difference 2.5, P <.001). Additionally, significant improvement in confidence scores for identification of risk factors and signs/symptoms of vasovagal response (mean difference 0.96, P <.001, and 0.46, P =.005) and LAST (mean difference 2.3, P <.001, and 2.2, P <.001) was noted. CONCLUSION: Implementation of an office emergencies curriculum significantly increased confidence in identification and management of unanticipated bleeding, anaphylaxis, vasovagal response, and LAST. Future studies evaluating knowledge-based assessments of learners are needed.